VITAMIN D DEFICIENCY PANDEMIC, A REALITY OR AN OVER DIAGNOSIS? NEED TO RETHINK VITAMIN D DEFICIENCY CUT OFF LEVELS - Afshan Bibi (Army Medical College Rawalpindi, 2020)
Objective: To determine clinical decision limits (cut off points) for vitamin D deficiency based on secondary hyperparathyroidism.